Zgodovina delovanja Društva za vakuumsko tehniko Slovenije - DVTS - Gasperič, Jože (Vakuumist, 1999)
In the paper the history of the Solvenian Society for Vacuum Technique and itsprevious organization, the Sevtion for vacuum technique at the Electrotehnical society of Slovenia in the last 40 yeras is described. particular chapters are dedicated to its main activities: education, publishing vacuum text books and the journal "Vakumist" (Vacuumist), organization of the professional meetings, excursions and visits to the well-known vacuum enterprises as well as organizing the parcipation of members in the International vacuum congresses, a collaboration with other vacuum societies and with the International Union for Vacuum Science, Techniques and Applications - IUVSTA and some other more importatnt activities.
Keywords: vakuumska tehnika; association; društva; zgodovinski pregledi